Comparative simulation study of PSA, VSA, and TSA processes for purification of methane from CO2 via SAPO-34 core-shell adsorbent. Issue 14 (21st September 2016) - Fakhroleslam, Mohammad; Fatemi, Shohreh
ABSTRACT: Cyclic adsorption processes of PSA, VSA, and TSA were modeled and numerically simulated using SAPO-34 core-shell adsorbent. The results were compared with ordinary SAPO-34 to achieve a more efficient process for CO2 –CH4 separation. OCM coupled with method of lines was used for numerical solution of the mechanistic model. The simulation results revealed higher efficiency of core-shell adsorbent with less usage of SAPO rather than the ordinary adsorbent to achieve the same degree of purification and recovery. VSA and TSA processes against PSA resulted in CH4 purification capability more than 99% with more than 73% recovery. However, VSA process has revealed higher productivity rather than TSA.